PEMBUATAN NUGET NABATI DARI KACANG MERAH DAN JANTUNG PISANG - Thrisna Arsy Widuri; Dewi Fortuna Ayu; Shanti Fitriani (SAGU, 2023)
The purpose of this study was to obtain the effect of the ratio of red beans and banana blossoms on the chemical and sensory characteristics of the nuggets and to obtain the selected treatment. The research method used a completely randomized design with four treatments and four replications, following the DMRT test at 5% level. The treatment in this study was the ratio between red bean and banana blossom with four levels; 40:60, 50:50, 60:40, and 70:30. Parameters observed were the moisture, ash, fat, protein, crude fiber content, and sensory evaluation. Results of the analysis of variance showed the addition of red bean and banana blossom significantly affected all parameters. The best treatment result is the ratio of red beans and banana heart 70:30 with a moisture content of 43.00%, ash content of 1.75%, fat content of 1.37%, protein content of 16.76%, and crude fibre content of 2.44%, and has a creamy colour, slightly chewy texture, and taste, aroma and overall preferred.